An Ion-Sensitive Field Effect Transistor Using Metal-Coordinated Zeolite-Templated Carbons as a Three-Dimensional Graphene Nanoribbon Network - Ishii, Takafumi; Horiuchi, Akihiro; Ozaki, Jun-ichi (Frontiers in Materials, 2019)
Zeolite template carbon (ZTC) is a carbon material composed of a three-dimensional network of graphene nanoribbons (GNR), and thus, is expected to exhibit electronic characteristics identical to those of GNR. ZTC is capable of doping heteroatoms in its structure, which offers the advantage of controlling its electronic properties by the presence of the heteroatoms. In this study, we prepared heteroatom-doped ZTCs and applied them to an ion-sensitive field effect transistor (ISFET), for investigating the effect of heteroatom doping on its electronic properties. The ISFET characteristics of un-doped ZTC include bipolarity, whereas oxygen-doped ZTC shows p-type semiconductor characteristics, and nitrogen-doped ZTC shows n-type characteristics. Furthermore, copper and nitrogen co-doped ZTC exhibits high sensor sensitivity (the change of electric conductivity reaches up to 50%) as a carbon-based ISFET. As a result of the analytical evaluation, a copper-nitrogen complex is formed in the co-doped ZTC, and the electronic interaction between copper and nitrogen atoms is able to change electrochemically. Owing to the presence of the copper-nitrogen complex, the co-doped ZTC shows specific ISFET characteristics.